CRIMINAL PROCEDURE REGULATIONS ON DISMISSAL OF THE INVESTIGATOR FROM PROCEEDINGS ACCORDING TO THE REGULATIONS OF THE CURRENT AND NEW CRIMINAL PROCEDURE CODES OF THE RA - Martirosyan, Arsen (State and Law, 2022)
The article discusses those legislative norms that allow the supervising prosecutor to dismiss the investigator from participating in criminal proceedings of the case.Within the framework of the study were analyzed the grounds for the dismissal of the investigator from proceedings, fixed both in the current and in the new Criminal Procedure Code. The author considers acceptable the approach that any violation of the law cannot be the basis for dismissal of the investigator from the proceedings, such an approach is fixed in the new Criminal Procedure Code of the Republic of Armenia.Within the framework of the carried out study were also identified the grounds fixed in the new Criminal Procedure Code of the Republic of Armenia for the dismissal of the investigator from proceedings, leading to a gross violation of the law.As a result of the carried out study, the author came to the conclusion that the new Code of Criminal Procedure more specifically sets out the grounds for the dismissal of the investigator from proceedings, which will undoubtedly exclude the possibility of applying such a prosecutorial act in case of any violation.
Keywords: investigator; criminal proceedings; criminal procedure; dismissal from proceedings; gross violation of the law; violation of the normal course of pre-trial proceedings